Building Satisfaction Through Trust: How Brand Image and Service Quality Shape Student Experience in Smart Gate Technology - Iva Mala; Yunus Handoko; Christea Frisdiantara (RISK : Jurnal Riset Bisnis dan Ekonomi, 2026)
This study examines the influence of Brand Image and Service Quality on Satisfaction Mediated by Trust (Student Smart Gate User Study). A quantitative method with the Structural Equation Modeling (SEM) approach using SmartPLS was applied to test the proposed hypothesis. The sample in this study consisted of 388 students obtained through purposive sampling. The results showed that brand image had a significant effect on satisfaction, while Servqual had no significant effect on satisfaction. Brand image was found to have an effect on trust, and the direct effect of Servqual on trust was significant. Trust was found to have a direct effect on satisfaction. In addition, trust was a full mediator in the relationship between brand image and satisfaction, and a partial mediator in the relationship between Servqual and satisfaction. The practical implications of this study are for Malang State University in managing Smart Gate including strengthening brand image through consistent communication to increase satisfaction and trust. Improving service quality is focused on system reliability and data security to build trust as a key determinant, thereby supporting operational efficiency and optimal student experience.